Digital Transformation In Corporate Finance: The Strategic Role Of IT In Driving Business Value - Kiran Bhujel; Iqbal Ansari; Kazi Sanwarul Azim; Suresh Shivram Panchal; Yogesh Sharad Ahirrao (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
The advent of digital transformation, facilitated by state-of-the-art IT systems, is changing the strategic paradigm of corporate finance by empowering organizations to attain increased efficiency, transparency, and nimbleness in the financial decision-making process. This article discusses how IT can serve as a strategic tool in generating quantifiable business value in the context of corporate finance departments, in particular its impact as a driver of capital allocation and risk management, forecast accuracy and value creation. The research employs a quantitative comparative study design synthesizing the secondary data found in the financial databases, industry benchmarks, and peer-reviewed case studies, and applications in the corporate treasury, capital budgeting, and financial reporting. Increased financial forecasting precision, operational cost reductions, and ROIC growth by 25-35%, 15-20%, and 12-18 percent, respectively, are indicators of success demonstrated by empirical evidence in the first three years of adoption by the organizations that implement IT-enabled digital transformation initiatives in the financial realm. The analysis also notes that integrated enterprise system, advanced analytics platform, and automation technologies can be used to increase working capital efficiency, ensure better regulatory compliance, and enhance stakeholder trust. The novelty in this research is entered by providing the linkage between how new technology may be adopted and how quantifiable corporate finance performance results are achieved. The research has developed a performance measurement framework that ties IT investment to the tangible and intangible business value. By integrating technical knowledge of IT systems with the strategic mindsets of finance, the study will serve the research domain of digital transformation with a feasible guide that the CFOs, finance strategists, and policymakers can consider. The paper ends with practical suggestions on governance, capability building and performance monitoring so that the digital transformation of finance can deliver sustained competitive advantage in an ever more technology-based economy.